Uniform Principal and Income Act, Section 5: Constitutionality of Its Retroactive Application - Lawrence P. King (Washington University Law Quarterly, 1960)
The allocation of stock dividends received by a trustee to either income or corpus has been a recurring problem perplexing the courts for many years. The competing principles, designated as the Pennsylvania, Massachusetts, and Kentucky rules have each gained judicial recognition, but not all problems created by the declaration of stock dividends have been solved.
Keywords: Dividends; Trusts and trustees